Gingival Temperature Variations in Dogs: Assessing Healthy and Inflamed Gingiva Using Thermal Imaging Before and During Anaesthesia - Özcan, Candemir; Yiğitarslan, Kürşad (Wiley, 2025)
ABSTRACTObjectivesThe aim of this study was to evaluate temperature differences in healthy (grade 0) and inflamed (grades 1 and 2) gingiva in dogs with varying gingival index (GI) scores, as well as the temperatures of different gingival regions (free gingiva [FG], attached gingiva [AG] and alveolar mucosa [AM]), using thermal imaging both before and during anaesthesia.Animal StudyThis study was carried out on 18 Golden Retrievers (males, n = 8; females, n = 10) aged 2–5 years (mean 3.25 ± 0.97 years) and weighing 15–29 kg (mean 22.35 ± 5.68 kg).ProceduresBuccal surface temperatures of the FG, AG, and AM were recorded using a thermal camera in dogs before and during anaesthesia. The GI was utilised to assess the levels of gingivitis in the anaesthetised dogs.ResultsThe difference in temperature between the maxillary and mandibular gingiva was quantified. Significant temperature variations were found between FG (Δt = 0.79 ± 0.23°C, p = 0.001), AG (Δt = 0.56 ± 0.21°C, p = 0.008), and AM (Δt = 0.56 ± 0.21°C, p = 0.009). There was a statistically significant temperature difference (0.72 ± 0.24, p = 0.008) between grade 1 FG and AG. High correlation (correlation coefficient (r) = 0.931, p < 0.01) between the room temperature measured and body temperature measured (r = 0.962, p < 0.01) before and during anaesthesia. No significant correlation was observed between gingival temperature measurements of the same sites before and during anaesthesia. There was no correlation between gingival temperature and body temperature measured before and during anaesthesia.ConclusionThis study shows local gingival temperature variations and the impact of environmental factors on body temperature during anaesthesia. The lack of correlation between gingival and body temperatures suggests that body temperature does not directly influence gingival temperature. These findings may help clinicians understand gingival health and temperature fluctuations. Further research is needed to determine the clinical significance and diagnostic value of gingival temperature changes.
Keywords: Veterinary medicine; dog; gingival index; infrared thermography; SF600-1100; temperature; Original Article; gingivitis